SOCIAL EMPOWERMENT TO DEAL WITH NEGATIVE STIGMA AND DISCRIMINATIVE TREATMENT AGAINST PEOPLE WITH HIV/AIDS - Argyo Demartoto; Siti Zunariyah; Tyas Nur Haryani (Jurnal Analisa Sosiologi, 2019)
The existence of people with HIV/AIDS or PWHAs in daily life results in a variety of social problems to themselves, family, friend, neighbor, surrounding environment, and wide society. This qualitative research with phenomenological approach aimed to analyze social empowerment to deal with negative stigma and discriminative treatment against PWHA in Surakarta, Indonesia. Primary data was collected from PWHAs, Solo Plus Peer Support Group, health workers, Surakarta AIDS Commission, and NGOs caring about AIDS. The result of observation, in-depth interview, and some related documents were analyzed using community empowerment theory and labeling. The result of research showed that social empowerment with intensive information education and communication on HIV/AIDS can change people’s interpretation on PWHAs. Government policy supporting PWHAs’ need, improved participation of PWHAs in such activities as HIV/AIDS overcoming in family, community, work environment, and society, and sustainable facilitation can solve social medical problem of PWHAs. The presence of improved capacity and social-cultural structure of society conducive to HIV/AIDS is expected to overcome negative labeling and discrimination against PWHA.     Keywords: PWHA empowerment, social economic and medical support for PWHAs AbstrakKeberadaan orang dengan HIV/AIDS atau ODHA dalam kehidupan sehari-hari menimbulkan aneka masalah sosial baik dengan dirinya sendiri, keluarga, teman, tetangga, lingkungan sekitar, dan masyarakat luas. Penelitian kualitatif dengan pendekatan fenomenologis ini bertujuan menganalisis pemberdayaan sosial untuk mengatasi stigma negatif dan perlakuan diskriminatif terhadap ODHA di Surakarta Indonesia. Data primer dikumpulkan dari ODHA, Kelompok Dukungan Sebaya Solo Plus, pelayan kesehatan, Komisi Penanggulangan AIDS Surakarta dan NGO peduli AIDS. Hasil observasi, in-depth interview, dan beberapa dokumen terkait dianalisis dengan teori pemberdayaan masyarakat dan labelling. Hasil penelitian menunjukkan bahwa pemberdayaan sosial dengan Komunikasi Informasi Edukasi yang intensif tentang HIV/AIDS dapat mengubah interpretasi masyarakat terhadap ODHA. Kebijakan pemerintah yang mendukung kebutuhan ODHA, meningkatnya partisipasi ODHA dalam berbagai kegiatan termasuk penanggulangan HIV/AIDS baik di keluarga, komunitas, lingkungan kerja dan masyarakat, serta pendampingan yang berkelanjutan dapat mengatasi masalah sosial medis ODHA. Dengan adanya peningkatan kapasitas dan struktur sosial budaya masyarakat yang kondusif terhadap HIV/AIDS diharapkan dapat mengatasi label negatif dan ketidakadilan terhadap ODHA.  Kata kunci : pemberdayaan ODHA, dukungan sosial ekonomi dan medis bagi ODHA